2017
DOI: 10.1007/s10661-017-5811-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating flood susceptible areas in inaccessible regions using remote sensing and geographic information systems

Abstract: Every summer, North Korea (NK) suffers from floods, resulting in decreased agricultural production and huge economic loss. Besides meteorological reasons, several factors can accelerate flood damage. Environmental studies about NK are difficult because NK is inaccessible due to the division of Korea. Remote sensing (RS) can be used to delineate flood inundated areas in inaccessible regions such as NK. The objective of this study was to investigate the spatial characteristics of flood susceptible areas (FSAs) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…Many studies using EO data for North Korea have been proposed for monitoring land use and land cover (LULC) over the Remote Sens. 2020, 12, 255 7 of 26 past several decades (for example, [51][52][53][54][55]). Furthermore, a number of government institutes and think-tanks have already established different types of thematic maps in North Korea using EO data (e.g., agricultural maps; deforestation maps; land cover maps, etc.).…”
Section: A Difficult-to-access Region: North Korea In the Contexts Ofmentioning
confidence: 99%
“…Many studies using EO data for North Korea have been proposed for monitoring land use and land cover (LULC) over the Remote Sens. 2020, 12, 255 7 of 26 past several decades (for example, [51][52][53][54][55]). Furthermore, a number of government institutes and think-tanks have already established different types of thematic maps in North Korea using EO data (e.g., agricultural maps; deforestation maps; land cover maps, etc.).…”
Section: A Difficult-to-access Region: North Korea In the Contexts Ofmentioning
confidence: 99%
“…North Korea is suffering from extreme forest degradation due to food and energy shortages [1][2][3]. Degraded and deforested lands are vulnerable to natural disasters, such as landslides and floods, which not only cause environmental damage, but also destroy agricultural infrastructure [1][2][3]. This results in a vicious cycle of degradation in the forest by woodcutting to address food and fuel shortages.…”
Section: Introductionmentioning
confidence: 99%
“…The inundations occurred mainly in a lower-order stream (1 and 2; 37.17%) and middle-order stream (3, 4 and 5; 58.61%). Therefore, it is once again confirmed that the DNS is an important factor in delineating FDAs in NK [17].…”
Section: Flood Damaged Area Delineationmentioning
confidence: 55%
“…Thus, the nearest-feature method of GRASS GIS 7.0.3 was used to delineate the nearest stream orders of FDAs and thereby determine whether flooding occurs in the mainstream or its branches. This information can be used to establish an improvement scheme [17]. The DEM was used to determine the stream order according to Hack's stream ordering method [49,50] using GRASS GIS 7.0.3.…”
Section: Delineation Of Flood Damaged Areasmentioning
confidence: 99%